ПІДВИЩЕННЯ ВІРУСОСТІЙКОСТІ РОСЛИН ЛЮПИНУ ЖОВТОГО ЗА ДІЇ МІКРОБНИХ ПРЕПАРАТІВ ТА ФІЗІОЛОГІЧНО АКТИВНИХ РЕЧОВИН - Пиріг, О. В. (Institute of Agrocultural Microbiology and Agro-industrial Manufacture of NAAS of Ukraine, 2016)
The influence of microbial preparations and physiologically active substances on the reproduction bean yellow mosaic virus in yellow lupine plants has been investigated. It was established that the action of microbial preparations on the limitation of the viral infection development is explained by the influence of exogenous physiologically active substances, which are contained in preparations and produced by the microorganisms introduced in agrocenosis, on the forming of endogenous phytohormone pool. Therefore, it optimizes a number of physiological processes of the plants and activates their defence reactions.